Livani glass factory in the twentieth century star hour: traditional glass design and development of the aesthetics of existence in space - Dūdiņa, Ilze (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Culture and other areas of life are started to being affected by trends of globalization. It is increasingly difficult to identify and preserve values of national culture and design which still existed in relatively recent past. The research object I have chosen is Latvian traditional glass design from the second half of the twentieth century. Livani’s glass factory contribution is not fundamentally, methodologically and regularly documented, however the products of this industrial design of such factory were a result of in-depth understanding about shape, color and material. The information about the century under perspective is fragmented and not systematic. At the same time design is an economic incentive to promote industrial growth, an aesthetic phenomenon and a symbol too. Personality and attractiveness, character, national characteristics and habits provide such a wide range of options that globalization cannot affect – or could it? Relevance of the report was based on several considerations: At the turn of the XX to XXI Century the interaction of design and political- economic rapidly entered the information space, and thus the minds of the people and everyday life. This period of time is a peculiar semiotic boundary to evaluate what passes by, as we can speak in the past tense about Latvian glass design in its industrial expression, therefore it is essential that it was fixed and documented. It is important to identify and collect information on Livani glass factory design products, designers and artists during the period of 1970-ies until the end of the century. It is now fixed the creators of Latvian industrial glass design in the period after World War II – Līvāni Glass Factory, which most successful period of producing design products was in Soviet times – 1970ies and 1980ies. One of the prerequisites that created the rapid increase of production and the elevation of certain level of quality was the reconstruction of factory in 1971. There was a production of colorful glassware series as well as creation of first crystal products. Quality glass and Livani glass designers who had an opportunity to carry out their own ideas and experiments carried out, was the reason of success, which ensured the export of factory's production as well. Experimental glass blower unit was established and together with technologists, artists and designers they provided the rise of artistic and technical level of Livani glass factory. Livani glass factory at that time became one of the leaders of Soviet Union in the manufacturing of glass and the remained in this position for several years. The Soviet era dictated strict rules for both producers and designers. To each design object a copyright certificate was issued, which needed to be approved in Moscow. It appeared that Livani Glass had acquired a stable position and lasting value at that time, its quality was solid. Looking back at the past and thinking about glass design development in perspective – there will always be an inevitable opportunity to begin again or continue, because there is always the first option, it is rooted in the genes, in archetypes, in the common memories and dreams of human beings, it promises the sense of returning home, sense of friendship and domesticity.